Analisis Strategi Manajemen Pendidikan Menggunakan School Based Management Terhadap Dinamika Pendidikan Formal - Sehan Rifky; Syahrini Devi; Uswatun Hasanah; Muhammad Safii (Departement of Mathematics Education, 2024)
Common problems in education management that occur at the formal education level include accessibility and equity, teaching quality, curriculum and evaluation, technology and innovation, human resource quality and many others. This research aims to analyse the relationship between the School Based Management method and the dynamics of formal education. Formal education refers to the education system organised in official educational institutions, such as schools and universities. The quality of education management is largely determined by the implementation methods used by the community in schools. The research method is used with a quantitative approach by collecting from some previous literature so as to form the idea of the latest thinking. The results of this study discuss that to get the quality of education management that is more well organised in formal education, using School Based Management has a relationship between school autonomy, stakeholders, performance improvement, evaluation and sustainability.